Identifying the challenges and opportunities of PCOS awareness month by analysing its global digital impact - Malhotra, Kashish; Pan, Carina Synn Cuen; Davitadze, Meri; , Team PCOS SEva; Kempegowda, Punith; Chu, Justin J.; Gleeson, Helena K.; Hebbar, Meghnaa; Jayaprakash, Sindoora; Khalil, Halimah; Lathia, Tejal; Melson, Eka; et al. (Frontiers in Endocrinology, 2023)
Background and objective: Although significant resources are invested each September for PCOS Awareness Month campaign, there are no studies measuring its impact. We evaluated the digital impact of PCOS Awareness Month, common themes and associated topics, top influencers, and global equity of influence during the PCOS Awareness month. Methods: In this serial cross-sectional analysis, we studied the outputs from Symplur® to study the total impressions of #PCOS on Twitter®. We tracked the hashtags—#PCOS, #PCOSawarenessmonth, #PCOSawareness—and a search query— “#PCOS OR #PCOSawarenessmonth OR #PCOSawareness”—using Sproutsocial® to study the total number of tweets related to PCOS Awareness Month. Network analysis was done using SocioViz® to identify common themes and associated topics. Using SymplurRank® machine learning algorithm, the top 10 #PCOS influencers were identified based on the number of mentions received. Google® Trends was used to study the web and news search popularity over the last 10 years beyond social media platforms. Results: An overall upward trend in the digital impact of PCOS awareness was noted since 2017. While the top themes associated with PCOS (insulin resistance, depression, anxiety, menopause, hormones, infertility) remained the same in 2021 and 2022, newer themes emerged in the latter year suggesting the need for ongoing review. News outlets were the most influential organisations during PCOS awareness months in both years of study. Seven of the top 10 users were the same in both years. Limited engagement from African, Asian, South American and non-English speaking European countries was seen on Google Trends analysis. Conclusion: Active involvement from various stakeholders of PCOS Awareness Month has shaped it into an effective strategy to raise awareness with social media playing a crucial role in amplifying the message. Our findings also provide an opportunity to understand the current perceptions and expectations amongst the public, which can influence future healthcare investment and research.